Paciente con enfermedad de Rosai-Dorfman-Destombes: 18F-FDG-PET/CT como herramienta diagnóstica - Araujo Cachay, LC (2022)
Rosai-Dorfman-Destombes disease (RDD) is a rare non-Langerhans cell histiocytosis, with sinus involvement and massive lymphadenopathy. RDD is usually self-limited